Synergistic chemotherapy/PTT/oxygen enrichment by multifunctional liposomal polydopamine nanoparticles for rheumatoid arthritis treatment - Xiaoling Fu; Yutong Song; Xianquan Feng; Zhihong Liu; Wenhao Gao; Hongtao Song; Qian Zhang (Elsevier, 2024)
Amultifunctional liposomal polydopamine nanoparticle (MPM@Lipo) was designed in this study, to combine chemotherapy, photothermal therapy (PTT) and oxygen enrichment to clear hyperproliferating inflammatory cells and improve the hypoxic microenvironment for rheumatoid arthritis (RA) treatment. MPM@Lipo significantly scavenged intracellular reactive oxygen species and relieved joint hypoxia, thus contributing to the repolarization of M1 macrophages into M2 phenotype. Furthermore, MPM@Lipo could accumulate at inflammatory joints, inhibit the production of inflammatory factors, and protect cartilage in vivo, effectively alleviating RA progression in a rat adjuvant-induced arthritis model. Moreover, upon laser irradiation, MPM@Lipo can elevate the temperature to not only significantly obliterate excessively proliferating inflammatory cells but also accelerate the production of methotrexate and oxygen, resulting in excellent RA treatment effects. Overall, the use of synergistic chemotherapy/PTT/oxygen enrichment therapy to treat RA is a powerful potential strategy.